Answer:
I have absolutely no clue sorry buddy
Step-by-step explanation:
There is no step-by-step explanation
-4x-2y=-12
4x+8y=-24
--------------------------add
6y = -36
y = -6
Substitute y = -6 into -4x-2y=-12
-4x-2(-6) = -12
-4x + 12 = -12
-4x = -24
x = 6
Answer
x = 6 and y = -6
Answer:
the answer is 50
Step-by-step explanation:
180-130=50
Step-by-step explanation:
A' (1,4)
B' (5,8)
C'( 5,4)
D' (3,2)
you're graph was hard to read. but basically turn all the negative x values of the original shape into positive x values